Online internship matching platform for universities in Terengganu using a User-Centered Design (UCD) approach - Mohamad Sharif, Muhammad Ilhan (2025)
The The Online Internship Matching Platform (OIMP) is a web-based system designed to assist in managing internship placement processes between students, companies, and administrators within universities located in Kuala Terengganu. The system was developed in response to the challenges of traditional internship matching methods, which were largely manual, inefficient, and lacked centralized coordination. Through the early phases of development, key issues such as delayed communication, scattered application tracking, and limited access to local internship opportunities were identified. As a solution, the OIMP was developed to streamline the internship matching process, reduce administrative workload, and enhance accessibility for students and companies. The system was developed using the Adapted Waterfall Model, which includes six sequential phases: planning, analysis, design, development, testing, and documentation. The design and interface of the system were guided by the User-Centered Design (UCD) theory, ensuring that user needs and expectations were prioritized throughout the development process. Functional modules for student registration, company internship postings, administrator approval, and real-time application tracking were successfully implemented. To evaluate system functionality, test cases and scenarios were used to verify that all features operate as intended. Furthermore, usability evaluation was conducted using the System Usability Scale (SUS) and UCD Metric-Based Evaluation to measure user satisfaction, effectiveness, and ease of use. A total of 34 respondents participated in the evaluation, and the results revealed a high level of user satisfaction with the system. The feedback and recommendations gathered from testers have been considered for future enhancements. Overall, the system has achieved its intended objectives and is expected to support a more efficient and structured internship process across academic institutions in Kuala Terengganu.